NILAI PENDIDIKAN AGAMA HINDU DALAM TEKS KEKAWIN NIRATHA PRAKERTA - Ni Ketut Setiari (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2021)
Literature (Susastra Veda) as a guide in determining the value of an action, covers very broad parts. In general, it is distinguished as Sruti and Smerti literature. They are both sruti and smerti, both of which are sources of dharma (truth). According to Hinduism, as described in the Vedas or its branches, human action begins and is based on the influence that comes from itself. In other words, the tendency of human behavior comes from an internal factor known as Tri Guna, namely three characteristics that are brought from birth: sattwam (calmness), rajas (dynamic nature), and tamas (laziness). In general, the form of human behavior is classified into three. The three behaviors are kayika, wacika, and manacika. Nirartha Prakreta is a work of Hindu literature in it, by Dang Hyang Nirartha, poured into the soul as reflected in Hinduism, classified into Hindu religious education values which are contained in the three basic frameworks of Hinduism called Tattwa, Susila and Ceremony. Therefore the assumption that can be emphasized here is that Kakawin Nirartha Prakreta contains the value of Hindu religious education which is contained in the three aspects of Hinduism, especially regarding Hindu morality (ethics).